Overtime Work Determinants of Men and Women in Slovakia - Považanová, Mariana; Kollár, Ján; Nedelová, Gabriela (Olsztyn Economic Journal, 2019)
The paper deals with the supply side of the Slovak labour market. The main goal of the present study was to examine what variables contribute to the explanation of working over-time (e.g. devoting more than 40 hours per week to paid work) separately for women and men. A binomial logistic regression was used and factors were identified separately for men and women. The data were drawn from the results of primary research conducted in the year 2018. Results suggest that the probability of working overtime is higher for both men and women with higher income. It seems that the substitution effect of an increase in income dominates the income effect. Household circumstances influence the probability of one’s working overtime. In those multi-member households where the husband has higher level of education than the wife, the husband will more likely work overtime and women will be less likely to work overtime. The presence of very young children in households has a significant impact on the reporting of women working overtime. Women with preschool children were less likely to work overtime than women in households in which there were older children or households without children.